2010
DOI: 10.4049/jimmunol.0902007
|View full text |Cite|
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Inhibit Human Th17 Cell Differentiation and Function and Induce a T Regulatory Cell Phenotype

Abstract: Mesenchymal stem cells (MSCs) exert immunomodulatory properties via the inhibition of T cell activation and proliferation. Because of the deleterious role of Th17 cells in the pathogenesis of inflammatory disease, we investigated whether proinflammatory cytokines could modify the expression of adhesion molecules on human MSCs, thereby contributing to increased Th17 cell adhesion to MSCs and, as a consequence, modulating the function of the latter cells. IFN-γ and TNF-α synergistically enhanced the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
416
2
9

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 509 publications
(453 citation statements)
references
References 48 publications
26
416
2
9
Order By: Relevance
“…Indeed some studies suggest that there is a requirement for IFN-g, and/or IL-1b in the activation of MSC immune suppressive functions [Ren et al, 2008], a finding that parallels repair in non-mammalian systems where inflammation is a prerequisite for regeneration [Young, 2004]. The differentiation of CD4 þ T cells to specific subsets is also influenced by MSC; with the mesenchymal cell skewing T cell responses towards regulatory patterns of cytokine secretion and concurrent suppression of Th1, Th2 or Th17 responses [Nemeth et al, 2009;Rafei et al, 2009;Ghannam et al, 2010]. These data are supported by elegant in vivo models of transplantation and autoimmune disease where MSC alter T cell polarisation away from the typical effector responses [Casiraghi et al, 2008;Ge et al, 2009;Rafei et al, 2009;Kavanagh and Mahon, 2011].…”
Section: Msc Suppression Of Adaptive Immunitymentioning
confidence: 99%
“…Indeed some studies suggest that there is a requirement for IFN-g, and/or IL-1b in the activation of MSC immune suppressive functions [Ren et al, 2008], a finding that parallels repair in non-mammalian systems where inflammation is a prerequisite for regeneration [Young, 2004]. The differentiation of CD4 þ T cells to specific subsets is also influenced by MSC; with the mesenchymal cell skewing T cell responses towards regulatory patterns of cytokine secretion and concurrent suppression of Th1, Th2 or Th17 responses [Nemeth et al, 2009;Rafei et al, 2009;Ghannam et al, 2010]. These data are supported by elegant in vivo models of transplantation and autoimmune disease where MSC alter T cell polarisation away from the typical effector responses [Casiraghi et al, 2008;Ge et al, 2009;Rafei et al, 2009;Kavanagh and Mahon, 2011].…”
Section: Msc Suppression Of Adaptive Immunitymentioning
confidence: 99%
“…MSCs also have unique immunomodulatory capacities (6). They can suppress T-cell proliferation in response to nominal antigens or alloantigens (7) and upregulate the number of regulatory T cells (8,9). MSCmediated immunosuppression is also associated with a reduction in inflammatory cytokine production (10).…”
mentioning
confidence: 99%
“…The steadily growing interest in MSC-mediated immunosuppression has involved its potential in the activation, expansion and induction of T reg cells from conventional CD4 + T eff cells both in vivo and in vitro [29][30][31]. We previously demonstrated that matrix metalloproteinases -2 and -9 secreted by MSCs play an important role in MSC- Fig.…”
Section: Discussionmentioning
confidence: 99%